Infraestrutura para implantação de empresas de base tecnológica: Parque Tecnológico de Ponta Grossa - Zammar, Gilberto (2010)
Technological Parks are institutions that are located on the border of two different worlds; for they intend to provide spaces that house both technology and innovative based companies, which are regulated by the logic of markets, and development, research, science and technology institutions which have policies related to education and production of scientific knowledge. They are distinct experiences, with different cultures and habits that will abide in the same area of development, but primarily they should establish an environment of integration and cooperation. Winning this paradigm of conflict between the academic and the business parts is the first challenge for the deployment of Technological Parks. These parks must be ableto absorb and promote the technological based businesses, characterized by technological innovation, the technological content of their products, processes and services as well as the use of modern methods of management. This paper presents an exploratory research to identify important factors for the establishment of Technology Parks, such as: Location, Focus, Management, Admission Criteria, Incubation, Land Tenure; Present Sectors: Software, Telecommunications, Science, Energy, Design, Environmental Technology and New Materials. The method used to analyze the results was Delphi. Through research it was possible to determine the best combination among the important factors in the deployment of the technology park. The most important factor among the identified factors was also determined. The main function of this research is to provide tools for decision making at the time of the implantation of the Technology Park in Ponta Grossa - PR.